Penggunaan Teorema Binomial dalam Menentukan Peluang Suatu Kejadian - Rektor Sianturi (Journal on Education, 2023)
The theory of opportunity arises from human activity which inspires bettors who try to find information on the chances of winning bets. Scientists who also like to play bets, experts make the theory of probability as a basic study of statistics and conduct mathematical analysis from a review of game examples. In this case, examine the toss of coins. To determine the probability of an event occurring in a coin toss, first calculate the number of sample points using the formula 2n where n is the number of sample spaces. In this case, the concept of the binomial theorem is used to determine the probability of an event occurring in the toss of a coin. The binomial theorem is very helpful in determining the probability of an event. Because it is very easy to determine the probability of an event is very rarely done.